Characterization of Archaeological Sediments Using Fourier Transform Infrared (FT-IR) and Portable X-ray Fluorescence (pXRF): An Application to Formative Period Pyro-Industrial Sites in Pacific Coastal Southern Chiapas, Mexico. Issue 1 (January 2016) - Neff, Hector; Bigney, Scott J; Sakai, Sachiko; Burger, Paul R; Garfin, Timothy; George, Richard G; Culleton, Brendan J; Kennett, Douglas J
Archaeological sediments from mounds within the mangrove zone of far-southern Pacific coastal Chiapas, Mexico, are characterized in order to test the hypothesis that specialized pyro-technological activities of the region's prehistoric inhabitants (salt and ceramic production) created the accumulations visible today. Fourier transform infrared spectroscopy (FT-IR) is used to characterize sediment mineralogy, while portable X-ray fluorescence (pXRF) is used to determine elemental concentrations. Elemental characterization of natural sediments by both instrumental neutron activation analysis (INAA) and pXRF also contribute to understanding of processes that created the archaeological deposits. Radiocarbon dates combined with typological analysis of ceramics indicate that pyro-industrial activity in the mangrove zone peaked during the Late Formative and Terminal Formative periods, when population and monumental activity on the coastal plain and piedmont were also at their peaks.